Метод оценки частоты выполнения фрагментов кода последовательной программы - Alexander Shalimov (Моделирование и анализ информационных систем, 2010)
The goal of this article is to consider the task of determining the execution frequency of program basic blocks. This task is important for such applications as program optimization, paralleling program execution, computing resources allocation, program compaction, and malicious software detection. A new method is proposed in the article for evaluation of basic block execution frequency based on the Monte Carlo method. The method proposed allows us to estimate a number of program runs to get the execution frequency with a given precision.